PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR METEMATIKA SISWA KELAS VII SMPN 11 PINGGIR - Malinda, Nora; Kartini, Kartini; Seregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study aims to improve the learning process and improve learning outcomes of the seventh grademathematics studentsof SMPN 11 Pinggir by implementing cooperative learning Numbered Heads Together (NHT) model. The subjects were students of seventh grade whom have heterogeneous academic ability. This research is a class act with two cycles. Each cycle has four stages, the stages are planning, implementation, observation and reflection. The results of the study show the observation sheet activities of teachers and students have done after the action. The improvements in the learning process of the students and an increasing number of students who achieve at UH KKM in the end of each cycle compared to the number of students who achieve a score of KKM on basic score. The results of this study indicate that the application of cooperative learning Numbered Heads Together (NHT) model can improve the process of learning and improve the learning outcomes of the seventh grademathematics studentsof SMPN 11 Pinggir of the semester of academic year 2013/2014.Keywords: Mathematics Learning Outcomes, Cooperative Learning, Numbered Head Together (NHT), Classroom Action Research.